Analisis Rating dan Harga Kamar Hotel Bintang Lima di Indonesia - Khaira Amalia Fachrudin; Dina Liviana Tarigan; Muhammad Faidhil Iman (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to determine and analyze the correlation between hotel ratings and room rates, as well as the differences in hotel ratings room rates among five-star hotels in cities that are popular and visited by many tourists, namely the city of Ubud, Mataram, Surabaya, Medan, Batu and Bantul. Research Methodology: This study uses descriptive research methods with correlational techniques. The test tools used are correlation test and One Way ANOVA test using SPSS software. The sample is 24 hotels. The data used is secondary data obtained directly from the Traveloka application. Results: The results showed that there was a positive and insignificant correlation between ratings and room rates; there is a significant difference among ratings in the cities of Ubud, Mataram, Surabaya, Medan, Batu, and Bantul ; and there is no significant difference among room Rates in Ubud, Mataram, Surabaya, Medan, Batu, and Bantul. Limitation: This study does not use the room rates of all room types, only uses the rates of Deluxe rooms because these types of rooms are owned by all hotels in the population. Contribution: Hotel managers need to improve comfort and service for hotel guests, hotel cleanliness, and food taste because these are factors that determine hotel ratings, and although not significant, these ratings are positively correlated with room rates that customers are willing to pay. Hotel managers with low ratings need to learn from hotels with higher ratings.  In Addition, managers need to take advantage of Electronic Word of Mouth (EWOM) such as reviews and ratings to achieve the success of an effective marketing strategy.